The effect of magnetite nanoparticles synthesis conditions on their ability to separate heavy metal ions - Bobik Magdalena (Archives of Environmental Protection, 2017)
Magnetite nanoparticles have become a promising material for scientific research. Among numerous technologies of their synthesis, co-precipitation seems to be the most convenient, less time-consuming and cheap method which produces fine and pure iron oxide particles applicable to environmental issues. The aim of the work was to investigate how the co-precipitation synthesis parameters, such as temperature and base volume, influence the magnetite nanoparticles ability to separate heavy metal ions. The synthesis were conducted at nine combinations of different ammonia volumes - 8 cm3, 10 cm3, 15 cm3 and temperatures - 30°C, 60°C, 90°C for each ammonia volume. Iron oxides synthesized at each combination were examined as an adsorbent of seven heavy metals: Cr(VI), Pb(II), Cr(III), Cu(II), Zn(II), Ni(II) and Cd(II). The representative sample of magnetite was characterized using XRD, SEM and BET methods. It was observed that more effective sorbent for majority of ions was produced at 30°C using 10 cm3 of ammonia. The characterization of the sample produced at these reaction conditions indicate that pure magnetite with an average crystallite size of 23.2 nm was obtained (XRD), the nanosized crystallites in the sample were agglomerated (SEM) and the specific surface area of the aggregates was estimated to be 55.64 m2·g-1 (BET). The general conclusion of the work is the evidence that magnetite nanoparticles have the ability to adsorb heavy metal ions from the aqueous solutions. The effectiveness of the process depends on many factors such as kind of heavy metal ion or the synthesis parameters of the sorbent.